Treści i programy przeznaczone dla ludności ukraińskiej w działalności Polskiego Radia dla Zagranicy oraz Polskiego Radia dla Ukrainy - Wielopolska-Szymura, Mirosława (Przegląd Wschodnioeuropejski, 2025)
The author analyzes the program offer and changes in the structure of Polish Radio, made to meet the information and cultural needs of Ukrainian citizens who were in a war crisis after Russia’s full-scale attack on Ukraine in February 2022. The activities of the language editorial offices operating in Polish Radio External Service were reviewed, the content offered by Polish Radio for Ukraine was analyzed, and the groups of topics related to Ukraine were characterized. The collected material confirms the assumption that the Polish public radio has undertaken the obligation to inform about Ukraine and the Polish public radio is involved in supporting Ukraine and its citizens, as well as helping to combat Russian propaganda and disinformation about the war in Ukraine.